Risk of malignancy in adrenal tumors in patients with a history of cancer - Samsel, Radosław; Nowak, Karolina; Papierska, Lucyna; Karpeta, Edyta; Roszkowska-Purska, Katarzyna; Smiertka, Wacław; Ostrowski, Tomasz; Chrapowicki, Eryk; Grabowski, Alan; Leszczyńska, Dorota; Cichocki, Andrzej (Frontiers in Oncology, 2023)
Purpose Adrenal gland is a common site of metastasis and on the other hand, metastases are the most frequent malignant adrenal tumors. The aim of this study was to estimate the risk of malignancy in suspicious adrenal mass in patients with a history of cancer. Methods This is a single-center retrospective analysis of patients with adrenal tumors treated previously for different types of cancers. Between 2004 and 2021 a hundred and six such patients were identified. Mean age of patients was 62.6 years (30-78), and mean time from oncologic treatment was 55.8 months (0-274). The most common primary cancer was kidney (RCC): 29 (27.4%), colon/rectum (CRC): 20 (18.9%) and lung (NSCLC): 20 (18.9%). Results Of 106 patients, 12 had hormonally active (HA) (11,3%) and 94 (88,7%) non active (HNA) tumors In group of patients with HA tumours 4 had hypercortisolaemia and 8 had elevation of urinary metanephrines. In the first group of HA patients pathology confirmed preoperative diagnosis of adrenocortical cancer and no metastasis was found. In all patients from the second group pheochromocytomas were confirmed. Primary (PM) and secondary (SM) malignancies were found in 50 patients (47.2%). In hormone inactive group only SM - 46/94 (48.9%) were diagnosed. The odds that adrenal lesion was a metastasis were higher if primary cancer was RCC (OR 4.29) and NSCLC (OR 12.3). Metastases were also more likely with high native tumor density, and bigger size in CT. The cut-off values for tumor size and native density calculated from receiver operating characteristic (ROC) curves were 37mm and 24, respectively. Conclusion Risk of malignancy of adrenal mass in a patient with a history of cancer is high (47,2%), regardless of hormonal status. 47,2% risk of malignancy. In preoperative assessment type of primary cancer, adrenal tumour size and native density on CT should be taken into consideration as predictive factors of malignancy. Native density exceeding 24 HU was the strongest risk factor of adrenal malignancy (RR 3.23), followed by history of lung or renal cancer (RR 2.82) and maximum tumor diameter over 37 mm (RR 2.14).